Height Measurement with Meter Wave Polarimetric MIMO Radar: Signal Model and MUSIC-like Algorithm - Zheng, Guimei; Song, Yuwei; Chen, Chen (Signal processing, 2022)
•Polarimetric MIMO radar, which combines the two advantages of polarization diversity and waveform diversity, is a subject worthy of in-depth study. This paper focuses on the height measurement with meter wave polarimetric MIMO radar. We filled the gap.•MUSIC-like algorithm are proposed for height measurement with polarimetric MIMO radar. The split beam question in MUSIC-like is found and the resolution is provided.•The proposed algorithms are also extended to long dipoles and large loop MIMO radar, which is the state-of-the-art research results. Inview of the advantages of polarization diversity and waveform diversity, polarimetric multiple-input multiple-output (MIMO) radar, which combines the two advantages, is a subject worthy of in-depth study. Height measurement is one of the key problems to be solved for meter wave radar. Therefore, this paper focuses on height measurement with meter wave polarimetric MIMO radar. First, we derive the height measurement signal model for flat ground reflection combined with the two diversity techniques. Then, we properly classify the signal model and modify it to make it suitable for the classical super-resolution height measurement algorithms, including the generalized multiple signal classification(MUSIC) algorithm and steering vector synthesis (SVS) MUSIC algorithm. The split beam question in SVS-MUSIC is found and the resolution is provided. The proposed algorithms are also extended to long dipoles and large loop MIMO radar. Moreover, the computational complexity of the two algorithms and the derivation of Cramer Rao bound (CRB) for polarimetric MIMO radar are given. These methods do not require decoherence. The innovation of this paper is to provide a height measurement signal model for meter wave polarimetric MIMO radar along with its effective solution. The simulation results prove the accuracy of this approach.